(untitled) (American Journal of Islam and Society, 1997)
Modem Orientalists generally boast of their objective analysis and impartial approach to problems, but facts believe their loud claims when their research comes down to the study of the Prophet. In this case, deep prejudices are reflected in their writings. Sometimes they indulge in frontal attacks on him, while at other times they hit him below the belt. They try to give an impression that the time in which the message of Islam was spread was ripe for revolution, independent of the Prophet. So to them, the Prophet’s contribution was to make a correct assessment of the prevailing situation and then make use of the opportunity provided to project his viewpoint. The ultimate aim of such endeavors on the part of Orientalists is to belittle the historic role of the Prophet and to unsettle the Muslim consciousness of its cognitive certainty of the divine revelation to the Prophet. The author asserts that the Prophet brought about a complete revolution in the lives of his early followers. After embracing Islam, they no longer remained the old Arabs they became God-fearing and pious folk who were very concerned with the life hereafter rather than riveting their attention on material considerations. In view of these realities, it is highly callous on the part of Reverend Watt to denigrate Muslims for what they sought to accomplish. No fair-minded historian would point out any character failing in these noble men. Also, they could not simply think of invading neighboring lands, as Watt would have us believe. Likewise, Watt’s whole chain of hypotheses about the economic and political reasons for the emigration to Abyssinia is without foundation ...